Molecular Magnetic Resonance Imaging of Lung Fibrogenesis with an Oxyamine‐Based Probe. Issue 33 (13th July 2017) - Waghorn, Philip A.; Jones, Chloe M.; Rotile, Nicholas J.; Koerner, Steffi K.; Ferreira, Diego S.; Chen, Howard H.; Probst, Clemens K.; Tager, Andrew M.; Caravan, Peter
Abstract: Fibrogenesis is the active production of extracellular matrix in response to tissue injury. In many chronic diseases persistent fibrogenesis results in the accumulation of scar tissue, which can lead to organ failure and death. However, no non‐invasive technique exists to assess this key biological process. All tissue fibrogenesis results in the formation of allysine, which enables collagen cross‐linking and leads to tissue stiffening and scar formation. We report herein a novel allysine‐binding gadolinium chelate (GdOA), that can non‐invasively detect and quantify the extent of fibrogenesis using magnetic resonance imaging (MRI). We demonstrate that GdOA signal enhancement correlates with the extent of the disease and is sensitive to a therapeutic response. Abstract : A key feature of fibrogenesis is the oxidation of lysine residues on collagen to give allysine, which is responsible for collagen cross‐linking, fibril formation, and scar tissue deposition in fibrotic diseases. The probe GdOA binds to allysine, enhancing its MRI signal in a fibrotic lung disease model and providing a quantitative readout of fibrogenesis.